Uncertainty and the signaling channel of monetary policy - Jenny Tang (Federal Reserve Bank of Boston, 2015)
This paper studies an environment where policy actions provide a signal of fundamentals to imperfectly informed agents. Closed-form solutions for optimal discretionary policy illustrate that this signaling channel can lead policymakers to maintain more stable inflation by linking policy accommodation to higher inflation expectations. This disciplining effect creates a benefit of central bank intransparency. The presence of this disciplining effect depends on the type of information signaled by interest rates and uncertainty levels determine its magnitude. The signaling channel is supported empirically by evidence that inflation forecasts respond more positively to surprise interest rate increases when forecast uncertainty is high.
Keywords: E52; 330